Effect of Angle of Rotation on the Rate of Electropolishing - M. El-Kashlan, Howaida; Ahmed, A.M. (Asian Journal of Chemistry, 2010)
The effect of angle of inclination on the rate of mass transfer was studied by measuring the limiting current of polishing of copper in phosphoric acid using parallel plate cell. Different factors were studied as phosphoric acid concentration, different angles of inclination and temperatures. Five concentrations of phosphoric acid were used, namely, 6, 8, 10, 12 and 14 M. Temperature was 23 ± 1 ºC. Different angle of rotations were used as 15º, 30º, 45º, 60º, 75º, 90º, 105º, 120º, 135º, 150º. The limiting current was found to increases by increasing angle of rotation in divided and undivided cell and limiting current decreases by increasing H3PO4 concentration. A comparison between the limiting current measured in divided and undivided cells shows that in undivided cells cathodic H2 evolution increases the anodic limiting current by an amount ranging from 4.8 to 42 % depending on acid concentration and angle of inclination.